The Influence of Service Quality and Customer Experience on Laptop Purchase Decisions Mediated by Consumer Motivation at Toko Rama Computer Lombok - Muhammad Rahmatullah Jayadi; Didy Ika Supryadi Jayadi (Journal of Accounting, Management, and Economic Development, 2026)
This study aims to analyze the influence of service quality and customer experience on laptop product purchase decisions mediated by consumer motivation at Toko Rama Computer East Lombok. The population in this study is all consumers who have purchased laptop products at least once at the Rama Computer Shop in East Lombok and are domiciled in East Lombok Regency. The sample totaled 105 respondents with purposive sampling technique. The research method used in this study is quantitative. This study is of a causal associative type, with the Structural Equation Model Partial Least Square (SEM-PLS) analysis technique using the SmartPLS 4.0 application. The results of the study show that: (1) service quality has a significant effect on purchase decisions; (2) customer experience does not have a significant effect on direct purchase decisions; (3) consumer motivation has a significant effect on purchase decisions; (4) service quality has a significant effect on consumer motivation; (5) customer experience has a significant effect on consumer motivation; (6) service quality mediated by consumer motivation does not have a significant effect on purchase decisions (no mediation); and (7) customer experience mediated by consumer motivation has a significant effect on purchase decisions (full mediation). These findings are to provide important insights for further research and can serve as a reference in emphasizing the importance of improving service quality and creating memorable customer experiences to drive consumer motivation and purchasing decisions.